2007
DOI: 10.1542/peds.2006-1993
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Implementation of Cystic Fibrosis Newborn Screening Programs: Cystic Fibrosis Foundation Workshop Report

Abstract: Newborn screening for cystic fibrosis offers the opportunity for early intervention and improved outcomes. This summary, resulting from a workshop sponsored by the Cystic Fibrosis Foundation to facilitate implementation of widespread high quality cystic fibrosis newborn screening, outlines the steps necessary for success based on the experience of existing programs. Planning should begin with a workgroup composed of those who will be responsible for the success of the local program, typically including the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 81 publications
2
108
0
4
Order By: Relevance
“…CF carrier testing has the potential to cause psychological harms as well as benefits; genetic counselling, to manage the effect of such harms, is therefore an important component of clinical practice. 23 These harms may influence relatives' decisions about carrier testing and therefore may explain to some extent the relatively low uptake of carrier testing that we report. Further investigation of the influences on relatives' decisions about carrier testing is needed.…”
Section: N¼716mentioning
confidence: 85%
“…CF carrier testing has the potential to cause psychological harms as well as benefits; genetic counselling, to manage the effect of such harms, is therefore an important component of clinical practice. 23 These harms may influence relatives' decisions about carrier testing and therefore may explain to some extent the relatively low uptake of carrier testing that we report. Further investigation of the influences on relatives' decisions about carrier testing is needed.…”
Section: N¼716mentioning
confidence: 85%
“…These aforementioned methods meet or exceed implementation, design, and reporting guidelines for CF NBS programs. 14 SCT results and diagnostic and clinical follow-up data are collected from CFCs via GDSP's secure, online screening information system. SCTs are performed by CFF-accredited laboratories according to current standards 15 and guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…After an abnormal IRT value is identified, most NBS programs perform DNA testing to identify known CFTR gene mutations (IRT/DNA strategy), while other programs repeat the IRT measurement in a second blood sample obtained from the infant at age approximately 2 weeks (IRT/IRT strategy) (Comeau et al, 2007). These strategies have been reported to provide approximately 90% to 95% sensitivity (Wilcken et al, 1995) and have identified newborns at risk for a wide spectrum of disease severity .…”
Section: The Use Of the Irt/irt Methods In Neonatal Screeningmentioning
confidence: 99%